Women in business contexts represented in the magazines Secretária Executiva and Mulher Executiva: a lexicogrammatical and visual analysis - Bernardon, Maura (2005)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.